The Saint-Narcisse morainic complex and early Younger Dryas events on the southeastern margin of the Laurentide Ice Sheet - Occhietti, Serge (Géographie physique et Quaternaire, 2007)
AbstractThe Saint-Narcisse morainic complex extends over 750 km along the southern margin of the Laurentian Highlands in Québec, north of the St. Lawrence Valley, between the Ottawa and Saguenay Rivers. To the east, the Laurentide Ice Sheet margin was located in the present St. Lawrence Estuary. To the west, the morainic complex is extended 235 km west of the Ottawa River to the Algonquin Highlands, in Ontario. The general outline of the morainic complex comprises large lobes and reentrants, related to major topographic features. In the lower Saint-Maurice River area, the moraine is composed of reworked clay and till and proximal glaciomarine deposits (Yamachiche Diamicton) and melt-out till and ice-marginal outwash (Charette Drift). The Saint-Narcisse Event can be subdivided in several phases: local readvance in low areas, main phase at the origin of the Saint-Narcisse Moraine s.s., melting-out of the marginal ice with compressive structures and large proglacial outwash features, and slow retreat with secondary ridges. The accuracy of the chronological data is limited by several factors: and a floating chronology is proposed. Two landmarks constrain the age and range of duration of the main Saint-Narcisse phase. The main ridge deposition occured after the onset, ca. 12.9 cal ka, of Champlain Sea in the St. Lawrence Valley, and a rapid ice retreat on the southern edge of the Laurentians. It ended before the drawdowm, in the Lake Huron basin, of Glacial Lake Algonquin ca. 12.5 cal ka. The Saint-Narcisse Event is related to the early cold phase of Younger Dryas, as evidenced by other YD ice readvances in Maine, Nova Scotia, and ice cover on the Gaspé Peninsula. It corresponds to a positive change of the budget of the Laurentide Ice Sheet as a result of climate forcing. After a slow ice front retreat during about 900-700 yr, the final phase of YD is marked by the Mars-Batiscan Moraine, located 17 to 70 km north of the Saint-Narcisse Moraine.